THE “POLETHICS” OF THE MEDIATED/TIZED SPECTATOR IN THE GLOBAL-TECHNOLOGIZED AGE: DAVID GREIG’S THEATRE - Verónica Rodríguez (Oxímora. Revista Internacional de Ética y Política, 2012)
Contemporary Scottish playwright David Greig’s dramaturgy has been concerned with the massive changes wrought across the world by neoliberal globalization in the last two decades. A political triple turn comprising ethics, the media and the spectator, and a shift between the notion “‘mediatized’ reiterative ‘expectator’” to “mediated performing spectator” within the “polethic” frame of ‘relationality’ in Greig’s works are argued in this article. It is further argued that the plays examined (Damascus, The American Pilot, Brewers Fayre and Fragile) use productive strategies like diffusion, reversibility and interchangeability, which foreground the asymmetries of the global/technologized age “polethically” mediating the global performing spectator.